Effect of hybrid SiO2@Ag nanoparticles with raspberry-like morphology on the excited states of the photosensitizers Rose Bengal and riboflavin - Martinez Porcel, Joaquin Emiliano (2019)
Metal nanoparticles (NPs) can strongly affect the photophysics of organic molecules through different mechanisms. To investigate the effect of silver nanomaterials on the triplet state dynamics of the photosensitizers riboflavin (Rf) and Rose Bengal (RB2−), we have here synthesized core–shell silica silver nanoparticles with raspberry-like morphology (SiO2@Ag NPs). For the synthesis of SiO2@Ag NPs from SiO2 nanoparticles a new combination of reported strategies was employed. The synthetic methodology involves in a first step SnCl2 as a precursor to obtain a homogeneous deposition of silver nuclei on colloidal silica spheres. In a second step, the growth of the silver nanoparticles is mediated by the photochemically generated ketyl radical of the substituted benzoin Irgacure-2959 (I-2959). Both Rf and RB2− dyes are adsorbed on the nanoparticles. Transient absorption spectroscopy experiments showed that there is a charge transfer process from the excited state of the adsorbed Rf to the silver nanoparticles. However, no similar reaction is observed for RB2−. These results are explained in terms of the expected equilibrium constants of the electron transfer for both dyes.